Dynamic changes of cultivated land use and grain production in the lower reaches of the Yellow River based on GlobeLand30 - Wang, Xiaowei; Cheng, Hui (Frontiers in Environmental Science, 2022)
Based on the data of GlobeLand30 in 2000, 2010 and 2020, this study studied the spatial distribution of cultivated land use and the cultivated land transfer pattern, the spatial distribution concentration degree and directional distribution characteristics of cultivated land and grain production, and the sensitivity analysis of grain production to the change of cultivated land area in the lower reaches of the Yellow River by using the methods of land cover transfer matrix, spatial distribution concentration model, sensitivity analysis model, standard deviation ellipse model and spatial autocorrelation analysis. The results show that: (1) The land type with the largest area transferred from cultivated land in the lower Yellow River is artificial surface, and its regional distribution is scattered; At the same time, the land type with the largest area transferred into cultivated land is still artificial surface, which is directly related to the rural land remediation measures implemented by the government. (2) During the period from 2000 to 2020, the spatial distribution concentration index (HHI) grade of cultivated land in the lower reaches of the Yellow River was moderately concentrated and below, and there was no obvious concentration trend; the concentration degree of grain production distribution in the lower reaches of the Yellow River is higher than that of cultivated land, such as Rizhao, Dongying, Qingdao and Weihai, where the HHI grades of grain production are higher. (3) During 2000-2010, the grain productions of 68.38% of districts and counties were insensitive to the change of cultivated land, while the grain productions of 18 districts and counties were highly sensitive to the change of cultivated land, mostly distributed in the hilly and mountainous areas of central and southern Shandong; During 2010-2020, the proportion of insensitive districts and counties decreased to 36%, and the middle and high sensitive areas obviously showed a gradual decreasing trend. Based on GlobeLand30 remote sensing image technology, this study can effectively reveal the temporal and spatial dynamic changes and provide scientific reference for further rational development and utilization of cultivated land resources in the lower reaches of the Yellow River.